Religion as a province of meaning the Kantian foundations of modern theology - Davidovich, Adina (Minneapolis Fortress Press, 1993)
The thought of Immanuel Kant has had incalculable - and, many would say, negative - impact on the modern estimation of religion, religious belief, and religious knowledge. Yet, Davidovich argues in the strikingly original interpretation, the chief lines and import of Kant's work on religion have been crippingly misunderstood. Davidovich radically refigures Kant scholarship by focusing decisively on his Third Critique, long thought his weakest, where she finds Kant confronting the results of his strong distinction between theoretical and practical reason. There he attempts a comprehensive theory of reflective judgment, in which contemplative thought of a moral designer of the universe is a principle that overcomes the bifurcation of scientific (rational) and moral (practical) activities. Moreover, this specifically religious consciousness, which harmonizes the lawfulness of nature with the purposiveness of freedom, is further developed, Davidovich maintains, by Rudolf Otto's and Paul Tillich's influential theories of religion. Today it can safeguard the status of religion and a normative science of religion. Davidovich's work is an outstanding contribution, breaking new ground in both Kantian scholarship and the theory of religion
The thought of Immanuel Kant has had incalculable - and, many would say, negative - impact on the modern estimation of religion, religious belief, and religious knowledge. Yet, Davidovich argues in the strikingly original interpretation, the chief lines and import of Kant's work on religion have been crippingly misunderstood. Davidovich radically refigures Kant scholarship by focusing decisively on his Third Critique, long thought his weakest, where she finds Kant confronting the results of his strong distinction between theoretical and practical reason. There he attempts a comprehensive theory of reflective judgment, in which contemplative thought of a moral designer of the universe is a principle that overcomes the bifurcation of scientific (rational) and moral (practical) activities. Moreover, this specifically religious consciousness, which harmonizes the lawfulness of nature with the purposiveness of freedom, is further developed, Davidovich maintains, by Rudolf Otto's and Paul Tillich's influential theories of religion. Today it can safeguard the status of religion and a normative science of religion. Davidovich's work is an outstanding contribution, breaking new ground in both Kantian scholarship and the theory of religion
Includes bibliographical references (p. [319]-328) and index
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: Kant, Immanuel -- 1724-1804 -- Religion; Otto, Rudolf -- 1869-1937; Tillich, Paul -- 1886-1965; Religion -- Philosophy -- History -- 19th century; Religion -- Philosophy -- History -- 20th century; Philosophical Theology